1991
DOI: 10.1002/j.1460-2075.1991.tb07655.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable deletion of exon 9 coding sequences in cystic fibrosis transmembrane conductance regulator gene mRNA transcripts in normal bronchial epithelium.

Abstract: The predicted protein domains coded by exons 9–12 and 19–23 of the 27 exon cystic fibrosis transmembrane conductance regulator (CFTR) gene contain two putative nucleotide‐binding fold regions. Analysis of CFTR mRNA transcripts in freshly isolated bronchial epithelium from 12 normal adult individuals demonstrated that all had some CFTR mRNA transcripts with exon 9 completely deleted (exon 9‐ mRNA transcripts). In most (9 of 12), the exon 9‐ transcripts represented less than or equal to 25% of the total CFTR tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
1
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(76 citation statements)
references
References 33 publications
5
66
1
4
Order By: Relevance
“…A dinucleotide repeat (TG) m was identified at the intron 8 -exon 9 junction with 10-12 repeats and a thymidine nucleotide tract ((T) n ) varying between 5 to 9 nucleotides. Notably, the two alleles analysed with T 5 correlated with expression of high amounts of exon 9-CFTR mRNA (Chu et al 1991). This was supported by a study of 124 individuals in which it was found that the shorter the poly-T tract the greater the relative amount of exon 9-CFTR mRNA transcripts present in respiratory epithelium .…”
Section: Class III Mutations Affecting Cl − Channel Regulation/gatingmentioning
confidence: 68%
See 1 more Smart Citation
“…A dinucleotide repeat (TG) m was identified at the intron 8 -exon 9 junction with 10-12 repeats and a thymidine nucleotide tract ((T) n ) varying between 5 to 9 nucleotides. Notably, the two alleles analysed with T 5 correlated with expression of high amounts of exon 9-CFTR mRNA (Chu et al 1991). This was supported by a study of 124 individuals in which it was found that the shorter the poly-T tract the greater the relative amount of exon 9-CFTR mRNA transcripts present in respiratory epithelium .…”
Section: Class III Mutations Affecting Cl − Channel Regulation/gatingmentioning
confidence: 68%
“…Exon 9 of the CFTR gene encodes the first 21% of NBD1 and is critical 1 Class VI may be re-named Class V following the re-classification by Welsh (2001). for CFTR function (Riordan et al 1989). RT-PCR analysis of bronchial epithelial cells from 12 non-CF individuals revealed that all samples contained some CFTR mRNA transcripts that were lacking exon 9 (exon 9-) (Chu et al 1991). The amount of exon 9-transcript varied in non-CF individuals between 0-92% .…”
Section: Class III Mutations Affecting Cl − Channel Regulation/gatingmentioning
confidence: 99%
“…Prior studies have demonstrated that a 5T variant, along with the preceding higher repetitive dinucleotide TG sequences such as (TG)13 or (TG)12, produces more mRNA transcripts with inframe deletion of exon 9. 11,15, 28 Groman et al 13 suggested that TG repeat number is a reliable predictor of penetrance for pathogenic 5T alleles. Those individuals carrying TG12-5T or TG13-5T were substantially more likely to exhibit an abnormal phenotype than those carrying TG11-5T.…”
Section: Cftr Polymorphisms In Chinese Males With Cbavd Wh Ni Et Al 688mentioning
confidence: 99%
“…As a control, the effect of TDP43 siRNA was tested on an unrelated hybrid minigene system containing exons 34-38 of the neurofibromin 1 (NF1) gene carrying a mutation that leads to the skipping of one or two exons. healthy individuals [16] (Fig. 2).…”
Section: Downregulation Of Tdp43 Rescues Endogenous Exonmentioning
confidence: 99%